Peradaban Islam Di Nusantara Masa Orde Baru Dan Perkembangan Pendidikan Islam - Ayu Andini; Moh Fathur; Anang Sholikhuddin (Universitas Negeri Gorontalo, 2026)
This study examines the dynamics of Islamic civilization in the Nusantara (Indonesian Archipelago) during the New Order era (1966-1998) and its implications for the development of Islamic education. The New Order period was characterized by contestation between state interests and Muslim aspirations in shaping national education. The method used is historical research with a qualitative-descriptive approach through literature study, policy document analysis, and review of primary and secondary sources. The findings indicate that although in the early New Order the state policy tended to marginalize political Islamic movements, over time significant accommodation toward Islam in educational policy occurred, marked by the enactment of Law No. 2 of 1989 on the National Education System and the establishment of ICMI in 1990. The transformation of madrasah from traditional institutions to modern educational institutions equivalent to public schools is an important achievement of Islamic civilization in Nusantara during this period. This study concludes that the development of Islamic education during the New Order was dialectical: on one hand subjected to state hegemony, but on the other hand it successfully utilized policy gaps to strengthen the identity and institutional framework of Islamic education.